公共健康倫理思考: Reflections on Public Health Ethics - CONG, Yali (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 公共健康倫理的溯源既不是醫學倫理學，也不是生命倫理學。本文從公共健康倫理發展遲緩這一現象入手，提出若真正理解公共健康倫理便需要真正理解公共衛生的特點和本質以及在公共衛生干預措施方面實踐公共健康倫理念。要概述一個令人滿意的公共健康倫理學理論還有困難，其核心價值群還需要補充和完善，以建立實質性公共健康倫理的基礎，例如需要準確界定群體、社區、人口、公共物品、共同利益、團結、互惠、福利、福祉和正義等概念和核心價值群，並從中西方不同的哲學倫理學視角進行比較研究。 Trace to the source of public health ethics is neither medical ethics nor bioethics. This paper begins by exploring the slow development of public health ethics and argues that a true understanding of public health ethics requires not only an understanding of public health itself, but also the inclusion of perspectives from the philosophy of public health, health economics and even political philosophy. Only then can we gain a deeper understanding of the characteristics and essence of public health, which in turn will help to highlight the ethical issues involved in public health interventions and public health ethics practice. It remains difficult to outline a satisfactory theory of public health ethics; however, the path to consensus requires a foundation of the core values of public health ethics. For instance, it is necessary to precisely define concepts such as groups, communities, populations, public goods, common interests, solidarity, reciprocity, welfare, well-being and justice. A comparative study of Eastern and Western philosophical and ethical perspectives would help us to gain a more profound understanding of these issues.